Cytokeratin immunostaining for detection of biliary epithelium: its use in counting bile ducts in cases of liver allograft rejection. Issue 4 (April 1994) - Harrison, R F; Patsiaoura, K; Hubscher, S G
Abstract : AIMS–To see how useful the application of a bile duct specific cytokeratin antibody (AE1) was in identifying and counting bile ducts in liver allograft biopsy specimens. METHODS–Eighteen liver biopsy specimens showing acute rejection and 17 biopsy specimens plus six hepatectomy specimens showing chronic rejection were studied. Serial sections were cut and stained with haematoxylin and eosin and AE1 antibody. Two pathologists (RFH and KP) examined the sections with respect to a range of histological features. RESULTS–Similar numbers of bile ducts were identified on haematoxylin and eosin sections as on corresponding sections stained by AE1 in cases of acute rejection and end stage chronic rejection. Greater numbers of bile ducts were identified by AE1 during the early stages of chronic rejection, especially when dense portal inflammatory infiltrates were present. These were often incomplete structures or individual cells within portal tracts, and bile ducts subsequently disappeared in all cases. Ductular proliferation was clearly shown by AE1 in acute rejection and the extent seemed to correlate with the severity of rejection present. By contrast, no ductular proliferation was observed in chronic rejection. CONCLUSIONS–Haematoxylin and eosin stained sections are adequate for counting bile ducts in most biopsy specimens from patients with suspected chronic rejection. Immunostaining for biliary cytokeratins using AE1 is of limited use in occasional cases where bile ducts are obscured by inflammatory cells.